2021
DOI: 10.1016/j.redox.2021.102040
|View full text |Cite
|
Sign up to set email alerts
|

Duchenne's muscular dystrophy involves a defective transsulfuration pathway activity

Abstract: Duchenne muscular dystrophy (DMD) is the most frequent X chromosome-linked disease caused by mutations in the gene encoding for dystrophin, leading to progressive and unstoppable degeneration of skeletal muscle tissues. Despite recent advances in the understanding of the molecular processes involved in the pathogenesis of DMD, there is still no cure. In this study, we aim at investigating the potential involvement of the transsulfuration pathway (TSP), and its by-end product namely hydrogen sulfide (H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 63 publications
3
18
1
1
Order By: Relevance
“…We noted a decrease in the expression of Atg5 , Atg7 , Becn1 , Map1lc3b , Lamp1 , and Sqstm1 genes in the gastrocnemius muscle, but in the diaphragm of 6-week-old mice, only Map1lc3b was reduced. Similarly to our study, Panza et al reported diminished expression of among others, Lamp1, Becn1 , and Atg7 , in quadriceps of 7-week-old animals [ 16 ] and the expression of Becn1, Map1lc3b, Lamp1 , and Sqstm1 was decreased in the same muscle of 22-week-old mice [ 11 ]. No difference in the mRNA levels of the Map1lc3a , Map1lc3b , and Sqstm1 genes was found between WT and mdx mice hearts [ 8 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We noted a decrease in the expression of Atg5 , Atg7 , Becn1 , Map1lc3b , Lamp1 , and Sqstm1 genes in the gastrocnemius muscle, but in the diaphragm of 6-week-old mice, only Map1lc3b was reduced. Similarly to our study, Panza et al reported diminished expression of among others, Lamp1, Becn1 , and Atg7 , in quadriceps of 7-week-old animals [ 16 ] and the expression of Becn1, Map1lc3b, Lamp1 , and Sqstm1 was decreased in the same muscle of 22-week-old mice [ 11 ]. No difference in the mRNA levels of the Map1lc3a , Map1lc3b , and Sqstm1 genes was found between WT and mdx mice hearts [ 8 ].…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, Whitehead et al noted that the use of simvastatin (an HMG-CoA reductase inhibitor, generally used to normalize cholesterol levels) has a positive effect on autophagy in the DMD mouse model [ 14 , 15 ]. Recently, restoration of functional autophagy in dystrophic skeletal muscle was also observed after treatment with a hydrogen sulfide donor [ 16 ]. Of note, it was also underlined that expression of mitophagy- and autophagy-related proteins may vary during mice lifetime [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, H 2 S may offer new pharmacological approaches for the management of sarcopenia. Indeed, it is well accepted the role of H 2 S in the physiopathology of SKM [ 14 , 20 , 27 ] but also in the pathogenesis of diabetes [ 50 ] and not last as an important mediator of inflammation [ 51 , 52 , 53 ]. Considering this evidence, we assessed the efficacy of endogenous or exogenous sources of H 2 S in an in vitro model of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence is reinforced by Terrill and colleagues, who observed a decrease in dystropathology and oxidative stress in L-cysteine-treated mdx mice [ 26 ]. More recent evidence demonstrates that, in myoblasts of DMD patients, there is an impairment in H 2 S signalling; indeed, a lowering in the gene expression of the CBS and CSE and H 2 S production was found [ 27 ]. Importantly, the exogenous replacement of H 2 S improves the molecular features of DMD in terms of inflammation and fibrosis in mdx mice [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sulfide salts could boost the local concentration of H 2 S in a short time, and they are considered as relative “clean” H 2 S donors due to no byproduct formation after H 2 S release. As a consequence, they are employed in a broad range of biological studies and exert beneficial pharmacological effects on central nervous system, cardiovascular system, alimentary system, male reproductive system, and many other related systems through a wide range of mechanisms 119,121,129–132 . However, due to the instantaneous H 2 S release characteristic of NaHS and Na 2 S, the desired release of H 2 S at a controlled rate within a long‐term period of time to specific organs, which mimics the endogenous H 2 S production, fails 118,119 .…”
Section: H2s Donors and H2s‐releasing Hybrid Moleculesmentioning
confidence: 99%